118k views
0 votes
What is the solution to the equation?

(A) d = –4 and d = 2
(B) d = –2 and d = 4
(C) d = 1
(D) d = 2
MY LAST QUESTION HELP.


What is the solution to the equation? (A) d = –4 and d = 2 (B) d = –2 and d = 4 (C-example-1
User Ajoy Sinha
by
4.5k points

1 Answer

4 votes

ANSWER

(C) d=1

Step-by-step explanation

The given equation is


\frac{ - 3d}{ {d}^(2) - 2d - 8} + (3)/(d - 4) = ( - 2)/(d + 2)

Factor the first fraction to get,


( - 3d)/((d + 2)(d - 4)) + (3)/(d - 4) = ( - 2)/(d + 2)

Multiply through by (d+2)(d-4)


- 3d + 3(d + 2) = - 2(d - 4)

Expand:


- 3d + 3d + 6 = - 2d + 8


6 = - 2d + 8


6 - 8= - 2d


- 2 = - 2d

divide both sides by -2


d = 1

User KumarA
by
4.6k points